Taking parents seriously: The experiences of parents with a son or daughter in adult medium secure forensic mental health care. (24th March 2018) - Finlay‐Carruthers, Gemma; Davies, Jason; Ferguson, John; Browne, Kevin
Abstract: Adult forensic mental health services provide care and treatment to individuals with complex offending and mental health histories. However, little attention has been paid to the parents of those receiving care within them. This research explored the experiences of parents with an adult son or daughter with mental illness in a medium secure mental health unit. Transcripts from semi‐structured interviews were analysed using interpretative phenomenological analysis. This led to the identification of three superordinate themes: 'Something's not right'—onset of mental distress; 'It's a terrible battle'—relating with professionals; and 'A very sad fact of life'—caring with no end in sight were identified which together contained nine subordinate themes. The onset of the mental distress was narrated as overwhelming, frightening, and confusing with experiences of violence. Services were seen as invalidating, and interactions with them characterized as a battle. Poor information and involvement were a common experience. Whilst diagnosis was a relief to some, the ongoing sense of loss and burden were clear. Staying connected and hopes for the future were also described. It is clear from this study that mental health services need to do more to engage and foster trust with parents from the outset and to offer support for this group. If secure services were to view parents as 'forensic carers', this may help improve respect and engagement between services and carers. Services and policymakers should strive to foster high‐quality family involvement as part of developing social inclusion.